2009
DOI: 10.1177/1403494808100939
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in consanguinity among parents of children born in Norway to women of Pakistani origin: A registry-based study

Abstract: In contrast to previous reports from the UK, our analysis suggests that there is a decrease in the proportion of consanguineously related parents of children born to women of Pakistani origin in Norway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
1
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 14 publications
0
19
1
2
Order By: Relevance
“…Registration in Norway has showed that 40% of second generation Pakistani, 17% of second generation Turkish and 7% of second generation Somali children have consanguine parents 3 , but the proportion has been decreasing over time. 19 It is likely that a similar pattern could be present in Denmark. Nevertheless, interpretation of the data without direct information on consanguinity still remains on tentative grounds.…”
Section: Discussionmentioning
confidence: 93%
“…Registration in Norway has showed that 40% of second generation Pakistani, 17% of second generation Turkish and 7% of second generation Somali children have consanguine parents 3 , but the proportion has been decreasing over time. 19 It is likely that a similar pattern could be present in Denmark. Nevertheless, interpretation of the data without direct information on consanguinity still remains on tentative grounds.…”
Section: Discussionmentioning
confidence: 93%
“…In Western Europe there are at least 10 million resident migrants from regions where consanguinity is preferential, and it is the possibility that the progeny of consanguineous unions are more likely to be affected by recessive genetic disorders that has aroused greater controversy, for example, with calls by some legislators for a ban on first-cousin marriages in the United Kingdom's Pakistani community (19,22). Although a decline in first-cousin marriage has been observed in the Norwegian Pakistani community (23), no similar trend seems to have occurred in the United Kingdom's Pakistani population (24) or in the Turkish or Moroccan communities in Belgium (25), and a rapid reduction in the preference for consanguineous unions by first-and second-generation migrant families in Europe appears improbable.…”
Section: Consanguineous Marriage (%)mentioning
confidence: 99%
“…The prevalence of consanguinity markedly declined in Europe, North America and Japan in the last century 25;26 , with a more recent reduction among some emigrant populations in 27 . This trend may be explained by acculturation of the immigrant community, with a gradual transition from their traditional consanguineous marriage preferences to those favoured by the dominant group in their adopted country 28 .…”
Section: Secular and Social Trends In Consanguineous Marriagementioning
confidence: 99%